Two new species of Entomobrya (Collembola, Entomobryomorpha) from the cave collembolan collection of Bonet from Asturias and Cantabria (north of Spain) - Jordana, Rafael; Baquero, Enrique (Zootaxa, 2006)
Two new species of Entomobrya are described from two caves of Asturias and Cantabria (north of Spain). The specimens were found in the Bonet collembolan collection at the “Museo Nacional de Ciencias Naturales” of Madrid (Spain). Entomomobrya boneti n. sp. was found in three slides containing 11, 4 and 1 specimens respectively, from the “Cueva del Castillo”, Puente el Viesgo (Santander). Entomobrya luquei n. sp. was found in a slide with 11 specimens from “Cueva de Cuetu-Lledías”, Llanes (Asturias). The species are described considering a set of 39 morphological and chaetotaxy characters. Both species appear to be troglophiles by the pigment reduction, although there are no other troglomorphic characters present. The gut content is composed of organic matter and fungus spores.